Analysis of The Impact of Net Promoter Score on Financial Performance With Customer Loyalty As Mediation - Hardianto, Bayu; Wijaya, Sieni (Ridwan Institute, 2023)
If we look at the increasing competition and market growth in every field especially in the professional services industry, customers have many choices, which puts organizations in a dilemma to find out what makes customers loyal to the company. People tend to tell negative stories more than positive ones, so understanding and mobilizing Promoters is critical to success. Net Promoter Score (NPS) is used in companies to measure a customer's desire to recommend a company's overall product or service to their friends or colleagues. NPS reflects customer satisfaction & has been shown to be an indicator of business growth potential. In this research, we will explain the relationship between Net Promoter Score and financial performance analysis of the impact of NPS score in IT firm in the last 5 years. The data collection technique used is to make an NPS survey that will be disseminated to existing customers of IT firm in the last 5 years who have purchased services / services as many as 93 customers with 218 Respondents. For variable (X) of this study is NPS, for variable (Y) is Financial Performance and for intervening variable (Z) is Customer Loyalty. The results indicate that NPS has a significant influence on Customer Loyalty, then Customer Loyalty has a significant influence on Financial Performance, and it can also be seen that there is a significant influence of NPS on Financial Performance.